Convivial Cultures in Multicultural Cities Polish Migrant Women in Manchester and Barcelona. - Rzepnikowska, Alina (Milton : Routledge, 2019)
The large-scale migration brought about by the expansion of the EU over a decade ago led to migration from less ethnically diverse countries to multicultural and super-diverse societies. This book examines the complex encounters between Polish migrant women and local populations in Manchester and Barcelona, with attention to the ways in which difference is negotiated and managed through everyday practices of conviviality, which help to overcome hierarchies and create elements of sameness. Illustrating how cultural differences may become important resources for interaction that facilitates positive relationships, Convivial Cultures in Multicultural Cities draws on the narratives of Polish migrant women to shed new light on everyday social relations between migrant women and local populations, including settled ethnic minorities and other migrants. In doing so, it contributes to our understanding of the positional nature of racial identification and complicates our ideas of whiteness and privilege.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Women immigrants -- England -- Manchester; Women immigrants -- Spain -- Barcelona; Cultural pluralism -- England -- Manchester; Cultural pluralism -- Spain -- Barcelona; Polish people -- England -- Manchester; Polish people -- Spain -- Barcelona; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General